Personality disorder is an excess risk factor for physical multimorbidity among women with mental state disorders. (November 2017) - Quirk, Shae E.; Stuart, Amanda L.; Berk, Michael; Pasco, Julie A.; Brennan Olsen, Sharon L.; Koivumaa-Honkanen, Heli; Honkanen, Risto; Lukkala, Pyry S.; Chanen, Andrew M.; Kotowicz, Mark; Williams, Lana J.
Abstract: We examined whether mental state disorders (lifetime mood, anxiety, eating, substance misuse) with comorbid personality disorder are associated with physical multimorbidity in a population-based sample of women. Mental state and personality disorders were assessed using semi-structured diagnostic interviews. Clinical measures were performed and medical conditions, medication use and lifestyle factors were documented by questionnaire. Mental state disorders were associated with higher odds of physical multimorbidity; risk was especially high for those with comorbid personality disorder. These findings suggest that mental state and physical comorbidity might be worsened by the additional comorbidity of personality disorder. Highlights: The relationship between mental state disorders and physical illness is well established. Less attention has been paid to the role of personality disorder. Mental state disorders were associated with physical multimorbidity. Risk was especially high for those with comorbid personality disorder.